Self‐assembled Protein Fibril‐metal Oxide Nanocomposites. Issue 7 (24th May 2017) - Levin, A.; Mason, T. O.; Knowles, T. P. J.; Shimanovich, U.
Abstract: Protein aggregation is commonly associated with the onset and development of neurodegenerative disorders, including Alzheimer's, Parkinson's and other forms of pathological disorders. While this phenomenon has historically been studied in the context of its relevance to human health, over the past decade significant research effort has focused on utilizing amyloid‐like protein assemblies as building blocks for the development of functional biomaterials and a number of protein‐based functional materials have been demonstrated. Here we extend this concept by synthesizing hybrid organic/inorganic microcapsules containing metal‐based NPs and protein nanofibrils as a nanocomposite. To this effect, we exploit the propensity of lysozyme to self‐assemble into amyloid nanofibrils and their functionalization by carboxyl‐modified Fe3 O4 NPs. We use a microfluidics‐based approach to control the micron scale moprhology of the newly formed nanocomposites. Our results illustrate the potential ofthis strategy as a platform for fabricating microcapsules from nanofibril‐inorganic NPs hybrid materials. Abstract :